Confederacin PerBoliviana - Anticona Sanchez, Haydee (2019)
He considers that the learning session is a work proposal that provides the necessary tools to the teacher to plan and dose according to the needs of the students, developing their cooperative learning through the formation of work teams in the classroom. The teacher raises the purpose of learning and for this she motivates and awakens the knowledge and previous knowledge using images and establishing trust and communication with the students during the motivation process, facilitating already structured charts and diagrams to achieve the purpose that the teacher enunciates in a time. determined. Students will know the criteria that will be evaluated. The evaluation and support during the activities carried out that are prescribed in the learning session will be noticeable. Finally, each team will explain with arguments and conclusions the essay that they previously prepared as a group to explain the processes of the Peru-Bolivian Confederation, thus achieving significant learning. The teacher provides feedback on the subject that needs to be specified and reinforced in the analysis of the sources and the explanation of the processes of the Peru-Bolivian confederation (1836-1839). Finished with the application of a metacognition card. The didactic sequence of the learning session: We elaborated a historical essay of the Peru Bolivian confederation (1836-1839) has its support from the theoretical bases of the constructivism of Piaget, Vygotsky Ausubel.